A study of the socio-economic development of the South Caucasus in the 19th – early 20th centuries in pre-revolutionary and soviet historiography - Almaz M. Ismailovа (Кавказология, 2022)
The article is devoted to the history of the socio-economic development researches of the South Caucasus in pre-revolutionary and Soviet historiography. This article determines the attitude of historians to the socio-economic situation in the South Caucasus in the XIX– early XX century. The ideas of the Caucasus, characteristic of the pre-revolutionary and Soviet schools, as a single historical and cultural region, as a region where there are all prerequisites for the development of the region’s economy, are highlighted.The summary of the researchers’ views, who note both the great ambitions of statehood and certain aspects of the socio-economic problems of the South Caucasus is conducted. The distinctiveness of Caucasian historiography is the study of works on individual areas, industries of the Caucasus, the complexity of the works written by them, an interdisciplinary approach to research. The peculiarities of the fact that the further development of Caucasian studies led to the differentiation of individual directions, to the isolation of various branches of Caucasian studies.The article studies the main trends of pre-revolutionary and Soviet historiography, notes various approaches to the assessment of historical experience, methodological principles of scientific research.It is concluded that despite the Russification and colonization policy of the tsarist government, there were progressive consequences of the socio–economic development of the South Caucasus, which was confirmed by historiographical studies of both pre-revolutionary and Soviet historians.